Effectiveness of Modernization Measures in Soviet Industry during Late 1960s - E. V. Bodrova; V. V. Kalinov; V. N. Krasivskaya (Научный диалог)
This article addresses the implementation of modernization initiatives in the Soviet Union's industrial sector during the late 1960s, focusing on several key industries. The analysis draws on declassified materials from the Central Committee of the Communist Party of the Soviet Union, now archived in the Russian State Archive of Contemporary History, which are introduced into scholarly discourse for the first time. The value of these documents is underscored by the fact that experts from the State Committee for Science and Technology accurately identified critical pain points and proposed legitimate mechanisms to overcome technological lag. It is demonstrated that the documents prepared by Soviet specialists responsible for industrial rearmament reflect a realistic understanding of the challenges at hand. The authors of these reports exhibited significant awareness and persistence in seeking to draw the attention of central management bodies to the most pressing issues that emerged in science and economics during this period, as well as a desire to offer practical recommendations grounded in both domestic and international experience. The authors conclude that, despite an understanding of the actual situation and scientifically substantiated recommendations, the state management system failed to overcome the entrenched sectoral approach, achieve interaction between the defense sector and civilian industries, or expedite the integration of research and development results into production.